Tauhid Sebagai Paradigma Pendidikan Islam (Studi Pemikiran Pendidikan Isma’il Raji al-Faruqi) - nasih, nasih nasih (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
Tauhid is the essence of the whole theory and practice of muslims in particular and humanity. Islamization of knowledge is meaningful if the effort is based on tauhid. It’s understood as an effort to affirm that Allah is one, the creator of nature and the controller of nature, thus all the mindsed and social activities of the community must be come from tauhid values. The values of islamic teaching summarized with the theory and practice of islamic education. This becomes a necessity for muslims to be separated from hegemony of the theory of secular education. Keywords: Islamic Education, Tauhid